Polymorphisms in gene MTHFR modify the association between gestational weight gain and adverse birth outcomes - Wu, Weixiang; Luo, Dan; Ruan, Xiaolin; Gu, Chunming; Lu, Weiming; Lian, Kailing; Mu, Xiaoping (Frontiers in Nutrition, 2022)
Evidence suggests a potential relationship between gestational weight gain (GWG) and adverse birth outcomes. However, the role of maternal genetic polymorphisms remains unclear. This study was conducted to investigate whether the relationship of GWG with risk of adverse birth outcomes was modified by methylenetetrahydrofolate reductase (MTHFR) polymorphisms. A total of 2967 Chinese pregnant women were included and divided into insufficient, sufficient, and excessive groups based on the Institute of Medicine (IOM) criteria. Polymorphisms of C677T and A1298C in gene MTHFR were genotyped. Multivariable logistic regression models were introduced after controlling major confounders. Excessive GWG was found to increase the odds ratio (OR) for macrosomia (OR = 3.47, 95% confidence interval [CI]: 1.86−6.48) and large-for-gestational age (LGA, OR = 3.25, 95% CI: 2.23−4.74), and decreased the OR for small-for-gestational age (SGA, OR = 0.60, 95% CI: 0.45−0.79). Pregnant women with insufficient GWG had a higher frequency of SGA (OR = 1.68, 95% CI: 1.32−2.13) and a lower rate of LGA (OR = 0.51, 95% CI: 0.27−0.96). Interestingly, significant associations of GWG categories in relation to low birth weight (LBW), macrosomia, and SGA were only suggested among pregnant women with MTHFR A1298C AA genotype. Among pregnant women with insufficient GWG group, an increased risk of 3.96 (95% CI: 1.57−10.01) for LBW was observed among subjects with the A1298C AA genotype, compared to the AC+CC genotype group. GWG categories are closely related to LBW, macrosomia, SGA and LGA, and the associations were modified by the polymorphism of MTHFR A1298C.